Island on the edge : Taiwan new cinema and after - Berry, Chris, 1959 April 28-; Lu, Feiyi (Hong Kong University Press, 2005)
This English-language anthology on Taiwan new cinema and its legacy covers all the major filmmakers from Hou Hsiao Hsien and Edward Yang to Ang Lee, bringing together a range of essays that analyze individual films produced since the advent of Taiwan new cinema in the early 1980s.